2021
DOI: 10.1021/acsnano.0c10159
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Nanomechanical Mapping of the Early Stages of Collagen Growth by Bimodal Force Microscopy

Abstract: High-speed AFM enabled the imaging of protein interactions with millisecond time resolutions (10 fps). However, the acquisition of nanomechanical maps of proteins is about 100 times slower. Here, we developed a high-speed bimodal AFM that provided high-spatial resolution maps of the elastic modulus, the loss tangent and the topography at imaging rates of 5.7 fps. The new microscope was applied to identify the initial stages of the self-assembly of the collagen structures. By following the changes in the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Since the density of collagen fibers appears to influence the second peak, it follows that this peak is likely related to the way collagen fibers are assembled within the gels, while the first peak being the same (within the bounds of experimental error), irrelevant of collagen density gels, is likely related to the gaps between fibrils (or areas of very low collagen fibril concentration) filled with liquid. Similar bimodal distribution of moduli was recently observed by Gisbert et al [26], who analyzed the changes in the mechanical properties associated with the early stages of collagen assembly on a mica surface (we note that the authors report much higher modulus values, which are most likely due to the effect of the substrate stiffness as only single fibers rather than a thick collagen gel layer were analyzed). Gisbert et al attributed the lowest moduli values to the gaps (between d-spacing) and the presence of monomers.…”
Section: Analysis Of Low-density and High-density Collagen Matrices B...supporting
confidence: 86%
“…Since the density of collagen fibers appears to influence the second peak, it follows that this peak is likely related to the way collagen fibers are assembled within the gels, while the first peak being the same (within the bounds of experimental error), irrelevant of collagen density gels, is likely related to the gaps between fibrils (or areas of very low collagen fibril concentration) filled with liquid. Similar bimodal distribution of moduli was recently observed by Gisbert et al [26], who analyzed the changes in the mechanical properties associated with the early stages of collagen assembly on a mica surface (we note that the authors report much higher modulus values, which are most likely due to the effect of the substrate stiffness as only single fibers rather than a thick collagen gel layer were analyzed). Gisbert et al attributed the lowest moduli values to the gaps (between d-spacing) and the presence of monomers.…”
Section: Analysis Of Low-density and High-density Collagen Matrices B...supporting
confidence: 86%
“…It involves the application of the virial theorem to excited modes. , This leads to two independent equations, one for each excited mode where z i is the deflection of the excited modes and z is the total cantilever deflection ( z ≈ z 0 + z 1 + z 2 ). In many situations of interest, T is well approximated by the period of the first eigenmode ( T ≈ T 1 ). , The above equation can be solved by two independent approaches. First, by integrating the equation of motion of the excited modes, it has been shown that for A 01 ≫ A 02 , We have used the subscript m to indicate that the virials are directly determined (measured) from the observables ( A 1 , A 2 , ϕ 1 , Δ f 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bimodal AFM is arguably the fastest and most versatile method for mapping the nanomechanical properties of surfaces and interfaces. , It has been applied to characterize the elastic properties of polymers, , hybrid materials, inorganic and organic crystals, , self-assembled monolayers, lipid membranes, DNA, , proteins, and cells . It combines high spatial resolution (angstrom or nanoscale) with quantitative accuracy for the determination of the Young’s modulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different ceramide localization in the membrane and mechanical properties is relevant in several biological contexts as apoptosis or viral infection. Finally, we will discuss possible approaches to evaluate the dynamic changes in viscoelasticity of lipid membranes [8], i.e., using fast mapping with bimodal AFM [9].…”
mentioning
confidence: 99%